Efektivitas Teknologi Financial (Fintech) dalam Mendukung Akses Keuangan Bagi Pelaku UMKM Di Kalangan Generasi Milenial - Victoria, Kareen; Septiani, Dhea; Azzahra, Ratumas Fadillah; Hati, Ilok Nyen Ratu Annisa Curah; Yossinomita, Yossinomita (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
This study examines the influence of financial literacy, financial technology (FinTech), and demographic moderation on the financial behavior of the Millennial generation in Indonesia. Employing a descriptive quantitative approach and the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS), data were collected from 97 respondents using a structured questionnaire. The analysis results reveal that financial literacy (X1), FinTech (X2), and demographic moderation (Z) have a significant impact on financial behavior (Y). Financial literacy directly enhances individuals’ ability to manage finances, invest, and plan for their financial future, with a P-value of 0.004. FinTech also promotes more efficient financial behavior, with a P-value of 0.009. Furthermore, demographic moderation significantly moderates the relationship between financial literacy and FinTech with financial behavior, with P-values of 0.002 and 0.035, respectively. These findings highlight the importance of incorporating demographic perspectives in understanding Millennials’ financial behavior. The research model demonstrates strong predictive capability, with an R-Square value of 0.766, indicating that 76.6% of the variance in financial behavior is explained by the independent variables. The constructs’ reliability and validity were well established, as evidenced by Cronbach’s Alpha and Composite Reliability values above 0.7, as well as an Average Variance Extracted (AVE) exceeding 0.5. Theoretically, this study contributes to the understanding of the relationship between financial literacy, FinTech, and demographic factors in shaping financial behavior. Practically, the findings suggest that FinTech service providers should design more inclusive strategies and implement effective financial education programs for Millennials. A comprehensive approach that considers demographic and technological factors is essential for enhancing financial literacy and behavior more effectively.